Travelling to the Secular or Journeying Inside The Self: Jurje Zaidane’s Gaze on European Modernity (Rihla Ila Oroba 1912, A Travel To Europe) - Tritha, Abdelaziz (International Journal of Language and Literary Studies, 2024)
Starting from his confrontational allegiance and parochial thesis, namely in his Essays and Lectures of William Robertson Smith(1912), William Robertson Smith discredits Arab travellers for their zealous keenness to discover Western cultural intricacies. He has examined the cultural practices and social kinships of Semite people and studied their theologies. William Robertson Smith went as far as to assume that “The Arabian traveller is quite different from ourselves. The labour of moving from place to place is a mere nuisance to him, he has no enjoyment in the effort, and grumbles at hunger or fatigue with all his might” (Smith, 1912, p: 498). My particular interest is in Jurje Zaidane’s Rihla Ila Oroba (1912) as a culturally inspired travel account to France and England. It is not only a voyage to discern the intricacies of the Western civilizational repositories but an interesting endeavour to demonstrate the long-standing tradition of Arabs’ presence in British and French cultural repertoire. His voyage shows the extent to which Arabs were inspired by Western modern logos. Jurje Zaidane minutely lingers on infinitesimal details of each country. I argue that this travel is a parallel occidentalist discourse that tries to create a counter-discursive narrative. Jurje Zaidane, from the perspective of a well-versed essayist, novelist and erudite traveller, cross-examines French and English cultural contexts. Ranging from the narration of public spaces to comments on French and English women, the journey towards the Other is vicariously shifted to Self-inquiry and discovery. Broached from a postcolonial micro-historicist approach, this paper aims at stultifying both the orientalist discourse and the occidentalist premise predicated on Hassan Hanafi’s allegiance to Occidentalism. This article concludes that Zaidane’s travel displays heterogeneous discourses that do not re-install sharp divisive between the East and the West.